Differential proliferative response of the ventral prostate and seminal vesicle to testosterone replacement - Justulin, L. A.; Ureshino, R. P.; Zanoni, M.; Felisbino, S. L. (Elsevier B.V., 2006)
We have investigated epithelial cell proliferation and the rate of glandular recovery of the ventral prostate (VP) and seminal vesicle (SV) promoted by testosterone replacement (TR) in castration-induced regressed glands. Adult male Wistar rats were castrated and, after 21 days, they were treated with testosterone propionate (4 mg/kg/day). Intact (CT) and castrated rats without TR (CS) were also analysed. VP and SV were processed for histochemistry, morphometric-stereological analysis and immunocytochemistry to determine the PCNA index (PI). After 10 days of TR, the VP weight reached similar to 72% of the CT values, while the SV weight exceeded similar to 17% of the CT values. By the third day of TR, VP and SV presented a mean P1 of 34% and 94% for distal region and 14% and 22% for proximal region, respectively. SV also had more luminal cells PCNA-positive than VP, mainly in the distal region. The PI values fell on days 5, 7 and 10, but were still higher than CT. These findings indicate that epithelial cells from involuted SV are more responsive to TR than those from VP when Stimulated to proliferate and replace the luminal cell population, suggesting a different mechanism regulating cell proliferation in response to androgenic stimuli. (c) 2006 International Federation for Cell Biology. Published by Elsevier Ltd. All rights reserved.
Keywords: proliferation index; castration; morphometry; androgen administration; PCNA